Use of advanced intravenous conscious sedation techniques in complex oral surgery procedures: Comparison of midazolam, midazolam‐propofol and midazolam‐propofol‐alfentanil combinations. (25th November 2021) - Offord, David J.; Kingsford, Nicola M.; Paterson, Ross; Mather, Craig I.; Robb, Nigel D.
Abstract: Aim: This retrospective observational study evaluates the safety and efficacy of intravenous sedation using midazolam only or combinations of two or three drugs including propofol and alfentanil for complex dental surgery such as implant placement or sinus augmentations. Methods: The study analyses 60 patients aged 42–79 who required advanced sedation techniques for complex oral surgery procedures. Twenty patients had midazolam only (M), 10 patients a 2‐drug combination of midazolam and propofol (MP) and a third group of 30 patients had the combination of midazolam, propofol and alfentanil (MAP). The last two regimens were carried out under the supervision of a dedicated consultant anaesthetist. Results: Higher mean minimum heart rate (beats/min) was observed in the midazolam group compared to the group sedated with the three‐drug regimen ( p < 0.05). The time between the last drug administration (LDA) and end of surgery (EOS) was significantly longer ( p < 0.005) in group M (≤45 mins) compared to the other two sedation groups MP and MAP (≤15 min). The final titration of midazolam of 11.2 ± 4 mg (5–20 mg) was significantly greater in group M than in either of group MP or MAP ( p < 0.05). Conclusion: In patients requiring conscious sedation to undergo complex and lengthy oral surgery, a combination of agents (midazolam, propofol and alfentanil) can provide a predictable steady state of sedation up to the end of the surgery resulting in better operating conditions for the surgeon and improved patient co‐operation. The shorter duration of action drugs propofol and alfentanil improved haemodynamic stability, sedation quality and reduce the final doses of each sedative agent.